Influencia de la red social facebook en la aplicación de la ortografía de los estudiantes de la carrera de Comunicación Social de la Universidad Técnica de Babahoyo - Ávila Izquierdo, Paola Estela (2018)
The most popular social networks are a source of innumerable benefits and advantages for their users, but they also generate unhealthy side effects. These can lead to serious problems for younger people who are still in the process of maturing and searching for personality. The influence of retouched content and comments without emotional filters that appear on social networks, are very harmful. It forces the most insecure to mold their personality to perfect prototypes that do not exist. An imbalance of the welfare and mental health of the users of these applications is generated. In the present investigation the problems that the social network of Facebook presents in the spelling of the students was evidenced, which was determined and verified by means of surveys and interviews directed to the authorities, teachers and students, in which it was concluded that in most of the writings the spelling is not respected and they adopt certain ways of cutting out words by suppressing letters or making strange connections of letters that express the idea or message. Faced with this situation, the alternative proposal was made, which consists in developing a program of talks to raise awareness of the good use of social networks and spelling to avoid creating vices in the writing of students and all members of the educational community in general.